EFFECT OF BODY WEIGHT AND SCROTAL CIRCUMFERENCE ON SEMEN PRODUCTION TRAITS IN CROSSBRED HOLSTEIN FRIESIAN BULLS - GOPINATHAN, A; SIVASELVAM, S N; KARTHICKEYAN, S M K; KULASEKAR, K (The Indian Journal of Animal Reproduction, 2022)
The present study aimed to investigate the influence of body weight and scrotal circumference and itsphenotypic correlation with semen production traits in crossbred Holstein Friesian bulls. Overall least-squaresmean for semen volume, sperm concentration, mass activity, initial sperm motility, post-thaw motility andnumber of doses/ejaculate were 4.10±0.06 ml, 842.7±21.7 million/ml, 2.11±0.03, 55.6±0.0%, 49.8±0.0% and196.92±5.4, respectively. The body weight and scrotal circumference of crossbred bulls influenced (p
Keywords: Body weight; Bulls; Phenotypic; Scrotal circumference; Semen